PENGARUH STRATEGI BISNIS DAN KEUNGGULAN BERSAING TERHADAP KINERJA PEMASARAN PADA USAHA KECIL MENENGAH SONGKOK ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œUDENG BALIÃƒÂ¢Ã¢â€šÂ¬Ã‚Â GENTENG BANYUWANGI - Ach Hasan Hasyim (Department of Sharia Economics, Faculty of Islamic Economics and Business, Universitas Islam Ibrahimy Banyuwangi, Indonesia, 2022)
The tight competition in the business world, makes SMEs must have a business strategy and competitive advantage, both in knowledge and enterpeneurship ability, the creation of a sustained competitive advantage will create superior marketing performance acceptable to consumers. This study examines the influence of business strategy and competitive advantage on the marketing performance of MSMEs songkok